Verification of a laser tracker with an indexed metrology platform. Issue 1 (April 2016) - Acero, R.; Santolaria, J.; Pueo, M.; Brau, A.
Abstract This work presents the development of a new verification procedure for laser trackers with an indexed metrology platform. The applicable standards which guide the calibration and verification procedures for laser trackers are ASME B89.4.19-2006, VDI/VDE 2617-2011 part 10 and the draft of ISO/CD10360-10 standard. All of them define a range of comparable tests for evaluating the performance of a laser tracker using calibrated artifacts for reference lengths definition. In this case, the use of an indexed metrology platform enables the evaluation of different working volumes of the laser tracker using the same physical calibrated gauge which remains still during the verification procedure; meanwhile, the laser tracker rotates with the platform. This is possible due to the six rotating positions of the platform and its ability to express points in a global reference system located in the lower platform. To overcome this, the kinematic modeling of the laser tracker is made together with its integration with the mathematical model of the platform. Then, the theoretical verification procedure of the laser tracker with the indexed metrology platform is developed, followed by an experimental phase where the verification procedure is carried out with a big dimension mesh of retroreflectors and a physical gauge which is used as a reference. The results obtained in the verification procedure validate the use of the indexed metrology platform in verification procedures for laser trackers, showing its advantages in terms of coverage of the instrument working volume, testing time reduction, and test setup simplification.